The process of government under Jefferson - Cunningham, Noble E., Jr., 1926-2007 (Princeton, New Jersey : Princeton University Press, 1978)
"Based on an exploration of the total mass of executive and legislative records for the years 1801-1809-something no other scholar has attempted-this thoroughly documented account describes the machinery and operation of the presidential office, the Cabinet, the departments, and other offices and commissions in the executive branch. It also explains the organization and processes of the national legislature. Cunningham has cleared away many errors and misconceptions, among them the claim that Jefferson was not interested in the normal process of day-to-day administration. In fact, Jefferson emerges as one of the most effective administrators ever to occupy the Presidency. This is an important and path-breaking study in administrative and legislative history." -Julian P. Boyd, Princeton UniversityOriginally published in 1978.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Contents -- List of Tables -- Preface -- I. A New Administration -- II. The President as Chief Executive -- III. Presidential Decisionmaking -- IV. The President's Cabinet -- V. The Making of the Annual Message -- VI. The Four Departments -- VII. The Executive Complement -- VIII. Appointments and Removals -- IX. Executive-Congressional Relations -- X. The Anatomy of Congressional Committees -- XI. A Deliberative Body -- XII. Parties and Pressures in Congress -- XIII. The Process of Petition -- XIV. The Jeffersonian Experience -- Appendix I -- Bibliographical Note -- Index -- Backmatter
Includes index.
Print version record.
eBooks on EBSCOhost
Keywords: Jefferson, Thomas, -- 1743-1826.; Jefferson, Thomas, -- 1743-1826.; Jefferson, Thomas, -- 1743-1826; United States -- Politics and government -- 1801-1809.; États-Unis -- Politique et gouvernement -- 1801-1809.; HISTORY -- United States -- 19th Century; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Politics and government; United States; 1801-1809